Low-power low-area beamformer design using switched-current ARAM using external capacitors. (February 2016) - Sharma, S.; Ytterdal, T.
Abstract: A switched-current (SI) based beamformer, suitable for low-power and low-area applications, is presented. The most important feature of the proposed beamformer is that the current consumption does not increase linearly with memory size. This is achieved by employing external capacitors for memory storage unlike a conventional SI memory. This is a fully differential design implemented using delay and sum approach. An Analog RAM (ARAM) has been used to implement the delay and each memory cell in the ARAM has been implemented using an SI circuits. There are 16 memory cells in each ARAM consuming 35.15 μA/cell. The signal-to-noise ratio (SNR) of 63 dB is measured after summation of 16 channels. The total current consumption of beamformer including the bias, and digital control is 9 mA and area is 1.27 mm 2 .